Designing Smart Objects to Support Affording Situations: Exploiting Affordance Through an Understanding of Forms of Engagement - Baber, Chris (Frontiers in Psychology, 2018)
In this paper I consider how the concept of ‘affordance’ has been adapted from the original writings of Gibson and applied to interaction design. I argue that a clear understanding of affordance shifts the goal of interaction design from one of solely focusing on either the physical object or the capabilities of the person, towards an understanding of interactivity. To do this, I develop the concept of Forms of Engagement, originally proposed to account for tool use. Finally, I extend this concept to interacting with modified tangible user interfaces, or ‘animate objects’. These animate objects not only sense how they are being used, but also communicate with each other to develop a shared intent, and provide prompts and cues to encourage specific actions. In this way, the human-object-environment system creates affording situations in pursuit of shared intentions and goals. In order to determine when to provide prompts and cues, the objects need to have a model of how they ought to be used and what intention they are being used to achieve. Consequently, affordances become not only the means by which actions are encouraged but also the manner in which intentions are identified and agreed.